A case of juvenile eosinophilic cholangitis: Rapid peripheral blood hypereosinophilia after admission leading to diagnosis. Issue 2 (10th November 2020) - Fukatsu, Shusaku; Kitamura, Katsuya; Asai, Yasutsugu; Nagai, Kazumasa; Kikuchi, Miho; Asano, Kyoko; Tadokoro, Kenichi; Yamanishi, Fumito; Tomita, Yusuke; Abe, Masakazu; Wada, Takuya; Matsue, Yubu; et al.
Abstract: A 15‐year‐old boy was referred to our hospital with elevated hepatobiliary enzyme levels and jaundice. Magnetic resonance cholangiopancreatography performed at the previous medical facility revealed a stricture of the intrahepatic and extrahepatic bile duct. Computed tomography showed dilatation and wall thickness of the intrahepatic bile ducts. Primary sclerosing cholangitis or cholangiocarcinoma was suspected. Endoscopic retrograde cholangiopancreatography (ERCP) showed stricture in the intrahepatic and extrahepatic bile duct. On admission, the eosinophil count in the peripheral blood was normal; however, rapid hypereosinophilia in the peripheral blood was observed after admission, leading us to suspect eosinophilic cholangitis (EC). A bile duct biopsy showed inflammatory cells and eosinophil infiltration during a second ERCP. The patient was diagnosed with EC based on histopathology. Abstract : Eosinophilic cholangitis was diagnosed based on the elevated blood eosinophil count after admission and bile duct pathology.